2019
DOI: 10.1002/aenm.201902077
|View full text |Cite
|
Sign up to set email alerts
|

Superior Lithium Storage Capacity of α‐MnS Nanoparticles Embedded in S‐Doped Carbonaceous Mesoporous Frameworks

Abstract: stability, power density, and safety. [1,3,4] Among the alternative electrode materials, transition metal sulfides (TMSs) are quite appealing due to their improved safety and high theoretical capacity (e.g., CuS: 560 mAh g −1 ; CoS 2 : 870 mAh g −1 ; and FeS 2 : 894 mAh g −1 , as calculated for the full conversion reaction). [4] Important, compared to other conversion materials, e.g., oxides, TMSs usually show improved electronic conductivity as well as faster reaction kinetics due to the weaker metal-sulfur b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 53 publications
3
98
0
Order By: Relevance
“…Apart from the main peaks in Figure A, several weak peaks located at region II are also found (Figure B). As reported previously, these feature peaks observed here could be attributed to the partial oxidation of Mn 2+ to a higher oxidation state of MnS 1+ z (0< z ≤1) and partial side reactions involving the Cu current collectors . What is more, the intensities and integral areas of the redox peaks in the subsequent CV profiles are almost identical to those in the second one, suggesting the excellent reversibility of the electrochemical reactions in the α‐MnS@ N ‐C/FG electrode.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Apart from the main peaks in Figure A, several weak peaks located at region II are also found (Figure B). As reported previously, these feature peaks observed here could be attributed to the partial oxidation of Mn 2+ to a higher oxidation state of MnS 1+ z (0< z ≤1) and partial side reactions involving the Cu current collectors . What is more, the intensities and integral areas of the redox peaks in the subsequent CV profiles are almost identical to those in the second one, suggesting the excellent reversibility of the electrochemical reactions in the α‐MnS@ N ‐C/FG electrode.…”
Section: Resultssupporting
confidence: 86%
“…For example, aw ell-defined a-MnS/S-doped carbon microrodc omposite prepared by Ma et al could retain 1383 mA hg À1 in the 300th cycle with good rate capability. [7] However,a lthough much progress has been made in recent years, the low-temperature (LT) performances of these well-architectured electrodes have rarely been investigated. Besides showinge xcellent cycle performance andr ate capacities at room temperature (RT), ad ecent performance at LT is also very significant for LIBs, especially if employedi ne xtreme environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, b = 0.5 representst he lithium ion insertion/extraction between carbon layers, whereas b = 1i sg enerally considered as ac apacitor behavior. [41] Twop eaks located at 0.01 Va nd 0.3 Va re used for kinetic analysis. It is found that b is about 0.49 for the sharp peak at 0.01 V, suggesting ad iffusion-controlled process.…”
Section: Resultsmentioning
confidence: 99%
“…The moderate porosity of Fe 7 S 8 @HD-C is in line with other MOF-derived materials previously reported by our group. [16] The carbon and iron sulfide content in the Fe 7 S 8 @HD-C composite were estimated by thermogravimetric analysis (TGA) measurements in oxygen ( Figure S4a, Supporting Information). The TGA curve exhibits multiple steps upon heating from room temperature to 800 °C.…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%